Changes in the circadian rhythm of metabolic rates in the saliva of patients with compensated type 2 diabetes mellitus - Gozhenko, A. I.; Hryshko, Yu. M.; Gorbach, T. V. (Journal of Education, Health and Sport, 2019)
In our previous studies, we have shown that salivary parameters differ during the day when one compares the morning and evening samples. That is, the analysis of biochemical components in saliva can be used to monitor the general state of the body’s health, which is especially important in metabolic disorders that occur in type 2 DM. It is possible to assume that the study of daily metabolic changes in patients with type 2 diabetes will help to determine the mechanisms of phenyl-butyric acid in this pathology. Patients with diabetes mellitus present with certain changes in saliva as compared to apparently healthy people. That is, although the daily rhythm of metabolism in saliva remains the same, the metabolic changes occur against this background. They are not significant, but their presence allows us to conclude that even in compensated type 2 DM, changes in metabolism are observed, and this can be explained by the disrupted carbohydrate metabolism with the mobilization of both lipid and protein metabolism. These changes can be observed in the parameters of metabolism in saliva and, especially in the form of a disrupted daily rhythm. Thus, even in compensated type 2 DM, there are changes in the energy metabolism, induced by hormonal regulation. These changes can be controlled using the daily saliva monitoring.